High speed low power phase accumulators for DDS applications in SiGe bipolar technology - Lämmle, Benjamin; Wagner, Christoph; Knapp, Herbert; Maurer, Linus; Weigel, Robert (Bipolar/BiCMOS Circuits and Technology Meeting, 2009. BCTM 2009. IEEE, 2009)
Two phase accumulators with 10 and 8 bit resolution, 7 and 15 GHz maximum clock rate, and a power consumption of 237 and 302.5 mW for use in direct digital synthesizers are presented. The accumulators are designed to retain phase coherency when a frequency switch is performed and are integrated into a DDS to perform simple measurement. The architecture is described, the circuits analyzed and measurements given. The chips are fabricated in a 0.35 mum 200-GHz fT SiGe bipolar technology and occupy only 1028 times 1128 mum2.
elib2cris::1512001600,laemmle2009b
Keywords: phase accumulator; phase accumulator; SiGe; heterojunction bipolar transistor; frequency synthesizer